Electrophysiological effects of edrophonium in the innervated and the transplanted denervated human heart. - Stemple, D R (1978)
In order to determine the mechanism of action of edrophonium on the cardiac conduction system, we used His bundle recording and pacing techniques to examine the electrophysiological effect of edrophonium in 6 patients undergoing diagnostic evaluation for coronary artery disease and in 9 cardiac transplant recipients who were free of acute graft rejection. After control measures were made of sinus cycle length, conduction intervals, and conduction system refractory periods, edrophonium was administered by constant intravenous infusion, and all electrophysiological measurements were repeated. In the normally innervated patients, edrophonium significantly increased sinus cycle length from 778 +/- 21 ms to 883 +/- 36 ms (P less than 0.01), AH interval from 88 +/- 11 ms to 100 +/- 12 ms (P less than 0.01), and AV nodal functional refractory period from 351 +/- 44 ms to 391 +/- 36 ms (P less than 0.05). In the patients with transplanted hearts, edrophonium had no electrophysiological effect other than increasing the cycle length of the remnant recipient atrium from 722 +/- 21 ms to 798 +/- 31 ms (P less than 0.01). We conclude that the electrophysiological effects of edrophonium in man are mediated primarily through autonomic innervation of the heart.